Paul and Asklepios: the Greco-Roman quest for healing and the apostolic mission - Stanley, Christopher D. (Library of New Testament studies, 2023)
"This book explores the nature and extent of sickness and healing in the Greco-Roman world, and assesses what the apostle Paul might have thought, said, and done regarding "pagan" modes of medical treatment"--